Persecution of Non-Monogamous Offenders in the Cancel Culture Phenomenon on Social Media - Muhammad Noval Abdul Rozak; Sri Kusumo Habsari; Eva Farhah (Universitas Negeri Surabaya, 2025)
Cancel culture is an act of mass cancellation or boycott experienced by public figures. Arawinda Kirana is one of the public figures who experienced cancel culture. She is considered to have committed an act of infidelity, which most netizens think is wrong. This research aims to reveal the form of power relations in the cancel culture phenomenon in social media. In Arawinda's case, data will be taken as screenshots in social media posts; then, a qualitative approach will be used to examine the data. This study found that cancel culture has a form of power relations between netizens and their targets. The netizen has the knowledge that tries to dominate the party, which is considered wrong. Generally, society is dominated by beliefs that believe that loyalty in intimate relationships is only in the form of monogamy. Infidelity as a form of non-monogamous relationship will be the target of public hatred. Therefore, if there are members of the public who are public figures, they will receive criticism, one of which is through cancel culture. The study employs thematic content analysis to classify collected data, revealing that cancel culture is driven by the belief that monogamous relationships are the only valid form.